Zwitterionic metal-organic frameworks modified polyamide membranes with enhanced water flux and antifouling capacity. (December 2022) - Wang, Chongbin; Wang, Hongchao; Li, Yongsheng; Feng, Yuanyuan; Liu, Zhong qiu; Zhao, Tian Sheng; Cao, Li
Abstract: Antifouling properties are considered to be crucial parameter to polyamide (PA) composite nanofiltration (NF) membranes for practical applications. In this study, an antifouling material, surface zwitterionization of Metal-organic frameworks (Z-MIL-101 (Cr)) was firstly prepared by decorating zwitterionic polymer onto the MOFs surface. Subsequently, a novel type of MOFs-based hybrid membranes were fabricated via mixing the Z-MIL-101 (Cr) nanoparticle with the organic matrix by interfacial polymerization technique. The most optimal hybrid membrane had a high water permeation of 26 L m −2 h −1 bar −1, which was 2.1 times higher than that pristine PA membrane, while the retention for Na2 SO4 was still kept at a considerably high value of 93%. The significant increased water flue can attribute to the existence of water channels generated by the Z-MIL-101 (Cr). More important, the antifouling property of the hybrid membrane was much better than that pristine PA, which was due to the formation of superhydrophilic liquid layer surrounding the zwitterionic groups. The combination of the micropore structure of the MOFs and the excellent antifouling properties of the decorated zwitterionic polymer effectively improved separation performances and antifouling ability, which makes these hybrid membranes promising for water purification. Graphical abstract: Image 1 Highlights: Zwitterionic metal-organic frameworks (Z-MIL-101 (Cr)) were prepared. Z-MIL-101 (Cr)-based hybrid membranes were fabricated via interfacial synthesis. The hybrid membranes show high water permeation of 26 L m −2 h −1 bar −1 . The antifouling ability of the hybrid membranes was significantly enhanced.